Land use/cover and eco-toxicity indices for identifying metal contamination in sediments of drains, Manzala Lake, Egypt - Muhammad A. El-Alfy; Yasser A. El-Amier; Toka E. El-Eraky (Heliyon, 2020)
Six heavy metals in three main drains along the East Nile Delta were estimated to assess the environmental risk and employ land use/cover map of each drain. Composite sediment samples (n = 3) were collected from each drain. The elements were analyzed by Atomic Absorption Spectrophotometer. The order of metal ions in the sediments of three drains of Manzala lake take the following order: Fe > Co > Ni > Cr > Cd > Pb in El-Serw drain, Fe > Ni > Co > Cd > Cr > Pb in Hadous drain and Fe > Cd > Ni > Co > Pb > Cr in Bahr El-Baqar drain. Studied Pollution indices indicate that drains discharged into Manzala Lake are mostly contaminated by metals. Geo-accumulation index showed contamination by Cd in all sites especially in site 13 of Bahr El-Baqar drain and low values to others. The mean probable effect level quotient showed percent of 21% in Hadous and El-Serw drains and 73% probability of being toxic in Bahr El-Baqar drain. The mean effect range median quotient also showed 21% in Hadous and El-Serw to 49% probability of being toxic in Bahr El-Baqar drains. Index of anthropogenicity impact indicate that the man-made activity either agricultural, industrial or fisheries impacted in the appearance of metal ions in the following sequence; Cd > Co > Pb > Ni > Cr. Hazard severity according to hazard quotient and modified hazard quotient of Ni and Cd take the following sequence; El-Serw < Hadous < Bahr El-Baqar drains. For Cr is; Hadous < Bahr El-Baqar < El-Serw and Pb is; Hadous < Elserw < Bahr El-Baqar drains. According to contamination severity index showed low for Pb, Ni and Cr and severe for Co and Cd which take the sequence of; Bahr El-Baqar > El-Serw > Hadous.